Design and analysis of a buck-boost converter circuit for piezoelectric energy harvesting system - Mostafa, Mohammad Golam; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The piezoelectric based energy harvesting technique needs to be improved as this system is highly capacitive rather than resistive which limits the current of a resistive load. The efficient way to harvest the energy from the system mostly depends on its interfacing circuitry. It is necessary to characterize and optimize the interfacing circuit for maximizing the output power. The circuit parameters - duty cycle, switching frequency, inductance and load resistance have been characterized and optimized to improve the efficiency of the harvesting system. The circuit has been simulated using PSpice (V16.5) electronic circuit simulation software. The input voltage of the circuit of the piezoelectric transducer is 0.54V AC in amplitude and the rated output voltage has been obtained as 3.3V. The results show that the maximum output power dissipated in the load is 57mW.